Integrating 31P DOSY NMR Spectroscopy and Molecular Mechanics as a Powerful Tool for Unraveling the Chemical Structures of Polyoxomolybdate‐Based Amphiphilic Nanohybrids in Aqueous Solution. Issue 18 (11th April 2014) - Shestakova , Pavletta; Absillis, Gregory; Martin‐Martinez, Francisco J.; De Proft, Frank; Willem, Rudolph; Parac‐Vogt, Tatjana N.
Abstract Novel organic–inorganic hybrids of various sizes were generated by reaction of 1, 8‐octanediphosphonic acid (ODP) and (NH4)6Mo7O24 in aqueous solution. The formation of rodlike hybrids with variable numbers of covalently bound ODP and polyoxomolybdate (POM) units can be tuned as a function of increasing (NH4)6Mo7O24 concentration at fixed ODP concentration. The chemical structure of the ODP/POM hybrids was characterized by 1H, 31P, and 95Mo NMR spectroscopy. Heteronuclear 31P DOSY (diffusion‐ ordered NMR spectroscopy) and molecular mechanics (MM) calculations were applied to determine the size and shape of the nanosized hybrids generated at various ODP/POM ratios. For this purpose, the structures of ODP/POM hybrids with variable numbers of ODP and POM units were optimized by MM and then approximated as cylinder‐shaped objects by using a recently described mathematical algorithm. The thus‐obtained cylinder length and diameter were further used to calculate the expected diffusion coefficients of the ODP/POM hybrids. Comparison of the calculated and experimentally determined diffusion coefficients led to the most probable ODP/POM hybrid length for each sample composition. The 31P DOSY results show that the length of the hybrids increases with increasing POM concentration and reaches a maximum corresponding to an average of 8 ODP/7 POM units per chain at a sample composition of 20 mM ODP and 14 mM POM. With excess POM, above the latter concentration, the formation of shorter‐chain hybrids terminated by Mo7 clusters at one or both ends was evidenced on further increasing the POM concentration. The results demonstrate that the combination of 31P DOSY and MM, although virtually unexplored in POM chemistry, is a powerful innovative strategy for the detailed characterization of nanosized organic–inorganic POM‐based hybrids in solution.